Teaching Towards “CDIO” Approach on Students of Electrical-Electronic Engineering Technology: A Case Study - Hong, Hoang Thi (VNU Journal of Science: Education Research, 2023)
Competence-based teaching model is a popular trend to replace traditional teaching in modern education. However, up to now, there has not been a competence approach model that provides a detailed and specific set of tools to help design and implement engineering training to achieve the desired learning outcomes like the “CDIO” (Conceive Design Implement Operate) approach. The papers used the experimental research method with the sample of 90 students (of whom 47 students were in the experimental class students and 43 students were in the control class) for the module "Electronic internship". It applied the teaching model with the positive teaching method through the process of organizing teaching and learning activities towards CDIO approach. The research result initially demonstrates that the use of CDIO-based teaching methods is valuable for teaching and learning in engineering training in general and in Electrical and Electronic Engineering Technology in particular.